Strategi Event Virtual Untuk Membangun Customer-Relationship Oleh Humas di Lembaga Pendidikan - Abdul Kholik; Chaira Armenitha; Iqbalul Lai Lika (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
Since the announcement of the COVID-19 pandemic which began in March 2020, the Indonesian government has begun to implement several rules to impose certain restrictions for various groups. Not only the business sector, government to education are not spared from activities that are usually carried out 'mainstream'.It is different with one of the educational institutions or rather an educational consultant named PT Edukasi Universal (Eduversal). Every year, Eduversal always holds special events to be attended by many students from various backgrounds and from various parts of Indonesia. Be it competitions such as the Eduversal Math Competition (EMC), the Indonesian Science Project Olympiad (ISPO), the Indonesian Language and Arts Olympiad (OSEBI), and others. Eduversal certainly needs to implement certain strategies in maximizing the events that have been held every year. Despite the pandemic, the program must be carried out even if it is brave. This is certainly done to maintain customer relations, especially for schools that have been loyal to following the programs at Eduversal.This study used descriptive qualitative method. This method is used to describe the social situation under study by covering aspects of knowledge and skills; processes and procedures; and the selection and development of applied technologies. The research data sources in this qualitative research regarding the Virtual Event strategy to build Customer-Relationship consist of primary data and secondary data. Primary data obtained from interviews with research subjects, namely PR PT. Eduversal, as well as other implementers involved in the activities held. The secondary data in this study is the data resulting from the documentation of the researcher's search in participating in the activities that are always held every year. The steps taken in analyzing the data from this research are classification, interpretation and conclusion.